WACANA KENABIAN SETELAH NABI MUHAMMAD SAW. - Armyn Hasibuan (SHAHIH (Jurnal Ilmu Kewahyuan), 2019)
Prophetic problems are the discussion in this paper that there are three sects that take part in discussing them namely Shia, Ahmadiyya Qodianiyah and Ahlu Sunnah wa al Jama'ah by giving birth to three conclusions : first, Prophethood can be considered final and they feel redundant to discuss it especially meaningless implications. Second, Prophethood exists and is open based on hadith and atsar. Third, there is integrity in which the interpretation of the cult sect is combined so that a new understanding is born of thinking as a field-to-philosophy study. A Prophet is not necessarily an apostle but an apostle is certain he is also a prophet. The Prophet and the Apostle alike gave an explanation for mankind so that humans are always on the path of truth like the path of divinity. The Prophet was a prominent man who was able to give news of eschatology and other things. According to TM Hasbi Ash Shiddiqi as quoted by Muhammad Daud Ali that the prophet who once led humans there were 124,000 people and apostles as many as 313 people, only 25 people were subordinated by Allah SWT. in the Quran. The fundamental difference between the prophets and apostles is t his duties as and functions, where prophets did not have the obligation to submit the form gained inspiration to mankind, while the apostles received revelation shall render to humanityProphetic problems are the discussion in this paper that there are three sects that take part in discussing them namely Shia, Ahmadiyya Qodianiyah and Ahlu Sunnah wa al Jama'ah by giving birth to three conclusions : first, Prophethood can be considered final and they feel redundant to discuss it especially meaningless implications. Second, Prophethood exists and is open based on hadith and atsar. Third, there is integrity in which the interpretation of the cult sect is combined so that a new understanding is born of thinking as a field-to-philosophy study. A Prophet is not necessarily an apostle but an apostle is certain he is also a prophet. The Prophet and the Apostle alike gave an explanation for mankind so that humans are always on the path of truth like the path of divinity. The Prophet was a prominent man who was able to give news of eschatology and other things. According to TM Hasbi Ash Shiddiqi as quoted by Muhammad Daud Ali that the prophet who once led humans there were 124,000 people and apostles as many as 313 people, only 25 people were subordinated by Allah SWT. in the Quran. The fundamental difference between the prophets and apostles is t his duties as and functions, where prophets did not have the obligation to submit the form gained inspiration to mankind, while the apostles received revelation shall render to humanity